Effect Concentration of Water Extract of Nerium oleander and Juglans nigra L. Allelopathy on Seed Germination and Radicle Length of (Silybum marianum) - Rozhgar Abdulla Rasul (مجلة ديالى للعلوم الزراعية, 2023)
An experiment was done to determine the allelopathic effects of Juglans nigra L. and Nerium oleander on the germination and radicle length of Milk thistle (Silybum marianum). The experiment was designed according to a completely randomized design (CRD). In this experiment, leaf-, hull-, and root extracts in two concentrations control, 5 and 10g L-1 was utilized. The experiment was conducted in a growth chamber with a temperature of 15 C0. After storing the seeds for 14 days, many characteristics were examined, including radicle length cm and germination rate percent. Concentrations of walnut and oleander extract had a substantial impact on every parameter under investigation. The results showed that the (T1) control treatment had the greatest germination and radicle length which were 70% and 20.08, respectively, compared with other treatments. A 10g L-1 extract concentration was used to measure the minimum values for two of the aforementioned parameters. It was found that (Juglans nigra L.) and Nerium oleander %10 extracts inhibit the growth of Silybum marianum and can be utilized to manage it in the field. However, more studies are needed to confirm the results.